Kajian Literatur Tentang Faktor-Faktor Yang Mempengaruhi Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pada Tenaga Kerja Konstruksi - Octavia, Salwa; Andriyani, Andriyani; Srisantyorini, Triana (Barongko: Jurnal Ilmu Kesehatan, 2025)
Unsafe behavior when carrying out work, such as ignoring or not using Personal Protective Equipment (PPE), has the potential to cause serious risks that can lead to death or material loss. Personal Protective Equipment itself is a device or equipment specifically designed to provide protection to the worker's body from various hazards that may occur during work activities, especially in high-risk environments such as the construction sector. Therefore, this research aims to conduct an in-depth literature review of the various factors that influence the level of compliance of construction workers in using PPE correctly and consistently while carrying out their duties. This study conducted a research method in the form of Literature Review.  The source of this research database is taken from Google Schoolar, Google Book, and Pubmed. This research was compiled from March 2025 to April 2025. The sources of this research meet the Inclusion Criteria, namely all sources used have been published in journals, are open access, and use Indonesian and English. The sources of this study were taken with a time frame of the last five years, starting from 2020 to 2024. The results of the Literature Review show that Age, Education, Knowledge, Behavior, OHS Facilities, HSE Inspection (Supervision), PPE Comfort, and OHS Policy have a significant relationship with the Behavior of Wearing Personal Protective Equipment (PPE) in Construction Workers. However, there is an insignificant relationship with the Working Period. It is hoped that these efforts will improve safety and reduce the risk of work accidents on construction sites.